Driving Industry 4.0 Maturity in Retail Manufacturing: A Case Study on IoT, Cloud, and RPA Integration - Sudhakar Reddipalli (International Journal of Computational and Experimental Science and Engineering, 2026)
Retail manufacturing faces unique operational challenges, including high-volume production requirements, perishability constraints, compressed profit margins, and comprehensive traceability mandates that distinguish it from traditional discrete manufacturing sectors. This article examines systematic Industry 4.0 transformation across greenfield dairy processing and case-ready beef manufacturing facilities through multi-year longitudinal case documentation. The transformation centered on enterprise resource planning systems as authoritative data sources while extending capabilities through Internet of Things sensor networks, cloud analytics platforms, mobile applications, and robotic process automation. Implementation utilized Scaled Agile Framework principles with product-oriented teams organized around manufacturing capabilities rather than application-centric structures. The architectural framework emphasized clean-core principles, maintaining system upgradeability and regulatory compliance while enabling innovation through carefully controlled extensions. Results demonstrate substantial improvements in operational equipment efficiency, supply chain performance, process accuracy, and administrative efficiency. Strategic outcomes include validated reusable templates enabling accelerated facility rollouts, risk reduction in subsequent implementations, and architecture reusability across diverse product lines. Critical success factors encompass enterprise resource planning-anchored architecture with edge extension, early investment in data contracts and integration standards, product-oriented delivery methodology adoption, and perishables-specific design considerations. The article establishes a comprehensive framework for retail manufacturing digital transformation that balances operational stability with innovation requirements while maintaining regulatory compliance and long-term system sustainability.